Guzarishi Kumitahi-yi Markazi-yi Hizbi Dimukrati Kurdistani Iran bah Kungirahi-yi Hashtum : (Hizbi Dimukrati Kurdistani Iran)
The Central Committee's report to the Eighth Congress of the Democratic Party of Iranian Kurdistan.